Final Income Tax: A Classic Contemporary Concept to Increase Voluntary Tax Compliance among Legal Professions in Indonesia - Tan, David; Sudirman, Lu (JILS (Journal of Indonesian Legal Studies), 2020)
Legal profession such as advocate, law consultant and civil law notary is a profession in law that plays a dominant role in providing legal services to the Indonesian public. By providing the legal services, they are entitled to receive honorarium in return. Empirical facts actually show that these legal professions’ tax compliance are still lacking. Main questions in this research are the legal aspects related to income tax on honorariums received by legal professions in connection with the legal services they provide and the concept of reconstruction to the laws and regulations related to income tax on honorarium received by legal professions. This research will answer the legal aspects related to the laws on income tax on these legal professions’ honorarium in Indonesia and the concept of reconstruction of the regulations related to income tax on these legal professions’ honorarium so that it may provide positive impetus to the legal profession’s tax compliance, and in turn contributes to the welfare of the nation. This normative juridical research approach is conducted using secondary data consisting of primary, secondary and tertiary legal materials. The aspects of the reconstruction are using the philosophical, constitutional and juridical paradigmatic studies with the Utilitarianism Theory by Jeremy Bentham, Progressive Legal Theory by Satjipto Rahardjo and Legal System Theory by Lawrence M. Friedman as basis of analysis. The results of this study found that there is a concept of contemporary reconstruction to the laws and regulations related to the income tax on honorarium received by legal professionals.